2017
DOI: 10.1039/c7ra00708f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contact angle on a reconstructive polymer surface by segregation

Abstract: A peculiar time evolution of contact angle of water on reconstructive polymer surface was analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The static contact angle of virgin PS was found to be 80 °, and increasing the concentration of PEG, the contact angle was decreased [25]. The PSP5 blend with 5% PEG concentration has demonstrated contact angle of 66 ° [26]. By increasing the concentration of PEG up to 10% in the PSP10 blend, the contact angle was found to be 63 ° [27].…”
Section: Contact Angle and Surfacementioning
confidence: 94%
“…The static contact angle of virgin PS was found to be 80 °, and increasing the concentration of PEG, the contact angle was decreased [25]. The PSP5 blend with 5% PEG concentration has demonstrated contact angle of 66 ° [26]. By increasing the concentration of PEG up to 10% in the PSP10 blend, the contact angle was found to be 63 ° [27].…”
Section: Contact Angle and Surfacementioning
confidence: 94%
“…Since the interfacial energy is lowered in the new chain arrangement, the droplet tends to increase the contact area with the surface, so the contact line moves outward, which triggers chain reconfiguration in the newly wetted area and further lowers the interfacial energy. [ 69 ] The wetting process continues, resulting in an elongating contact line and decreasing contact angle. In the meantime, water adsorption happens on the interface due to the strong interaction between the metal–ligand coordination sites and the water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In short, the thickness ( t 1 ) and Gaussian roughness at the surface (σ 1 ) of the dPMMA film were determined to be 67.6 and 0.2 nm, respectively. Fitting analysis based on a sublayer model revealed that the PMEA layer with a thickness ( t 2 ) of 12.9 nm at most was formed on the dPMMA film after the treatment. Also, since the Gaussian roughness of 0.9 nm at the PMEA/dPMMA interface was greater than the 0.2 nm at the air/dPMMA interface or the dPMMA surface, it seems most likely that PMEA chains were diffused into the surface region of the dPMMA film.…”
Section: Resultsmentioning
confidence: 99%